Continuing to teach in a time of crisis: The Chinese rural educational system's response and student satisfaction and social and cognitive presence. (18th June 2021) - Wang, Jing; Yang, Yuqin; Li, Hongli; van Aalst, Jan
Abstract: This research consisted of two studies to investigate how the Chinese rural educational system supported students' online learning and to determine the factors that influenced students' online learning quality (satisfaction and cognitive and social presence) during the COVID‐19 pandemic. Study 1, based on interviews with three curriculum officers, seven principals and 30 course teachers, found that great efforts were made to realize digital equity and education for all students. The necessity of providing resources and support to teachers and students (facilitating conditions) was recognized, along with the importance of teachers' online course design and organization and the facilitation of discourse (teaching presence and social presence). Based on the findings of Study 1 and the literature review, a conceptual model of facilitating conditions and teaching presence reported to influence students' online learning quality was generated. In Study 2, 1, 409 students from three rural primary schools were surveyed to test the conceptual model. The results indicated that facilitating conditions influenced students' online learning quality through enhanced technology self‐efficacy and perceived usefulness. Teaching presence directly and positively predicted students' online learning quality. This research highlights the importance of creating a learning community and providing technology access and support to ensure online learning opportunities and quality for rural students. Practitioner notes What is already known about this topic Chinese students from rural or migrant schools have fewer opportunities to access computers and the Internet, lower frequencies of online activity and technology self‐efficacy and less training and parental and teacher support. Providing support and resources to encourage and facilitate technology use among teachers and students in rural and underdeveloped schools is of great importance. Identifying the factors that contribute to online learning quality among rural school students to tackle the transition to online learning is necessary. What this paper adds The rural government and schools have made great efforts to ensure digital equity and education for all students, despite family conditions. Facilitating purposeful interactions and providing timely feedback is critical for effective learning in online teaching. Facilitating conditions represented by available support and resources and teaching presence influence students' online learning quality in rural areas. Implications for practice and/or policy Providing digital equipment and resources to all students is the first step towards distance learning. Providing opportunities to improve teachers' digital competency is critical for providing quality online instruction. Providing students timely assistance and useful and learner‐friendly technologies to enhance their satisfaction and social and cognitive presence is necessary. Online instructors should create a friendly online learning environment, facilitate active discussion and purposeful reflection and create opportunities to promote students' open communication, group cohesion and meaning construction.